Proteomics in cardiovascular disease: clinical considerations - Delles, Christian (Henry Stewart Talks, 2013)
Systems biology, Definition of proteomics, Proteomics: rationale and practical aspects, Proteomics in cardiovascular pathophysiology, Proteomics to detect biomarkers of cardiovascular disease, Urinary proteomics using capillary electrophoresis / mass spectrometry, Proteomics of coronary artery disease, Proteomics of pre-eclampsia, Proteomics of other cardiovascular diseases: stroke, heart failure, diabetic nephropathy